Latvian co-operatives: Agents of vertical coordination? - Timea Török; Jon H. Hanf; Zanete Gruzina (Journal of Co-operative Studies, 2010)
Vertical coordination has become increasingly important in the agri-food business in countries such as Latvia, making the use of contractual arrangements such as marketing and production contracts more common. In this work, we analyse the use of these contracts in the Latvian agri-food sector. Because of the Latvian dualistic production structure, which consists of more small farms and fewer large farms, we pay particular attention to co-operatives in this region and evaluate whether co-operatives can act as agents of change by linking small farms to vertically coordinated chains.
Keywords: 630